2008
DOI: 10.1210/jc.2007-0353
|View full text |Cite
|
Sign up to set email alerts
|

Association of Low Sodium-Iodide Symporter Messenger Ribonucleic Acid Expression in Malignant Thyroid Nodules with Increased Intracellular Protein Staining

Abstract: We confirmed that reduced NIS mRNA expression in thyroid malignant nodules is associated with strong intracellular protein staining and may be related to the inability of the NIS protein to migrate to the cellular basolateral membrane. These results may explain the low iodide uptake of malignant nodules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 15 publications
2
24
0
3
Order By: Relevance
“…Previous reports have shown predominantly intracellular localization of NIS protein in thyroid tumors (30)(31)(32).…”
Section: Discussionmentioning
confidence: 87%
“…Previous reports have shown predominantly intracellular localization of NIS protein in thyroid tumors (30)(31)(32).…”
Section: Discussionmentioning
confidence: 87%
“…NIS expression was localized in the lumen side of the seminiferous ducts and Leydig cells but not observed in Sertoli cells with immunohistochemical examination (6). Interestingly, Sodré et al (13) reported low NIS mRNA levels in malignant thyroid nodules, and also it was expressed intracellularly. The weak expression of NIS mRNA in testicular tissue may be reason of less concentrated radioiodine.…”
Section: Discussionmentioning
confidence: 97%
“…Reduced TSH-R may also cause low NIS mRNA levels and deficient NIS migration (Sodre et al, 2008). Activation of BRAF, Ras and RET decrease NIS mRNA.…”
Section: Nis In Thyroid Cancermentioning
confidence: 99%